The Synge letters : Bishop Edward Synge to his daughter Alicia, Roscommon to Dublin, 1746-1752 /: Bishop Edward Synge to his daughter Alicia, Roscommon to Dublin, 1746-1752. (2012) - Synge, Edward, -1762; Cooper, Alicia Synge, 1733-1807
No abstract available